Comparative Optical Behaviour of High and Low Index Cladding Contrast Bragg Fiber - Narendra Bihari; Ritesh Kumar Chourasia (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
We investigate and evaluate the optical performance of high- and low-RI cladding contrast Bragg fiber for two design wavelengths: 1550 nm (in the near-infrared region) and 632.8 nm (in the visible range). In order to establish a connection between the incoming and outgoing light waves using the transfer matrix technique, the boundary matching approach is used. Less periodic cladding layers are needed to create a perfect photonic band gap (PBG), and the measured PBG in high RI cladding contrast Bragg fiber (HRCCBF) are rather large. Both low refractive index and high refractive index spectra of PBG Cladding contrast Bragg fiber (LRCCBF) performance is very sensitive to the incoming light's optical path, or angle of incidence. One way to find out how sensitive the Bragg fiber is for sensing applications is to measure the PBG's thickness or spectral shift. As the design wavelength increases, the spectral bandwidth of PBG with core RI changes, and HRCCBF seems to be quite sensitive to this shift. When taking the Left Band Edge (LBE) and the Right Band Edge (RBE) into account, LRCCBF is much more sensitive than HRCCBF, making it the better choice for sensing applications.
Keywords: Bragg Fiber; Transfer Matrix Method; Photonic Band Gap; High Contrast; Design Wavelength